ANALISIS KADAR VITAMIN D PADA MAHASISWA INSTITUT KESEHATAN MEDISTRA DAN MAHASISWA FAKULTAS KEDOKTERAN GIGI UNIVERSITAS SUMATERA UTARA - Miftahul Zannah; Yahwardiah Siregar; Ariyati Yosi (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2019)
Vitamin D levels influenced by many factors like formation, nutritions, malabsorbtion and degradation of 25(OH)D. Formation factors is one of important for metabolism vitamin D. Vitamin D is the main hormone regulating calcium phosphate homeostasis and mineral bone metabolism. Loss of muscle mass and fraity are prevalent in many chronic disease. The study group consisted of 31 samples from Institut Kesehatan Medistra (n=12) and Fakultas Kedokteran Gigi USU (n=19). Vitamin D levels were measure with ELISA (Diagnostic Biochem Canada). Most age for student Institut Kesehatan Medistra is 21 years old and student Fakultas Kedokteran Gigi USU is 22 years old. Frequency of Vitamin D level student Institut Kesehatan Medistra is 91,7% (deficiency) and student Fakultas Kedokteran Gigi USU 84,2%(deficiency). There was significant difference in vitamin D levels between two group with significant (p=0,018).